2015
DOI: 10.1002/ana.24540
|View full text |Cite|
|
Sign up to set email alerts
|

GATA1‐mediated transcriptional regulation of the γ‐secretase activating protein increases Aβ formation in Down syndrome

Abstract: Because of an extra copy of the Aβ precursor protein gene on chromosome 21, Down syndrome (DS) individuals develop high levels of Aβ peptides and Alzheimer disease–like brain amyloidosis early in life. Here we show that the γ-secretase activating protein (GSAP), a key enzyme in amyloidogenesis, is increased in DS brains and specifically regulated at the transcriptional level by GATA1 transcription factor. The discovery of this novel pathway has translational implications for DS, because pharmacological inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 25 publications
(75 reference statements)
0
20
0
Order By: Relevance
“…The discrepancy in 16 kDa GSAP levels between DS and AD (present findings) could be related to the presence of an extra copy of the APP gene in DS that might stimulate the expression of GSAP or other confounding components such as transcription factors [9, 22]. Data indicate that formation of the 16 kDa GSAP active form depends on caspase-3 [9], an apoptotic marker that is elevated and highly expressed in neurofibrillary tangles and plaques, in both human AD and animal models of this disease [21]. Although previous investigations indicate that 16 kDa GSAP levels are associated with Aβ deposition [5, 6], here we found that GSAP protein levels did not correlate with amyloid and NFT scores either in the frontal cortex or hippocampus across clinical groups.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The discrepancy in 16 kDa GSAP levels between DS and AD (present findings) could be related to the presence of an extra copy of the APP gene in DS that might stimulate the expression of GSAP or other confounding components such as transcription factors [9, 22]. Data indicate that formation of the 16 kDa GSAP active form depends on caspase-3 [9], an apoptotic marker that is elevated and highly expressed in neurofibrillary tangles and plaques, in both human AD and animal models of this disease [21]. Although previous investigations indicate that 16 kDa GSAP levels are associated with Aβ deposition [5, 6], here we found that GSAP protein levels did not correlate with amyloid and NFT scores either in the frontal cortex or hippocampus across clinical groups.…”
Section: Discussionmentioning
confidence: 97%
“…The discrepancies between these findings and ours may be related to differences in methodologies, study design and/or cohorts examined. Interestingly, levels of the full-length 98 kDa and active 16 kDa GSAP forms were significantly increased in the frontal cortex of patients with Down Syndrome (DS) compared age-matched controls [9]. The discrepancy in 16 kDa GSAP levels between DS and AD (present findings) could be related to the presence of an extra copy of the APP gene in DS that might stimulate the expression of GSAP or other confounding components such as transcription factors [9, 22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30) The expression level of the transcription factor, GATA1, which is located on chromosome X, has been reported to be altered in DS patients. 31) Further studies are required to determine the detailed mechanism of the decreased NEP expression in DS patients.…”
Section: Discussionmentioning
confidence: 99%